Chemoselective oxidant-free dehydrogenation of alcohols in lignin using Cp*Ir catalysts. Issue 7 (25th November 2015) - Zhu, Rui; Wang, Bing; Cui, Minshu; Deng, Jin; Li, Xinglong; Ma, Yingbo; Fu, Yao
Abstract : Hydrogen gas was captured from native lignin using the catalyst Cp*Ir and the dehydrogenative lignin could be further degraded with the help of Zn & NH4 Cl through a two-step one pot process. Abstract : A remarkably effective method of chemoselective dehydrogenation of alcohols in lignin has been developed with an iridium catalyst. An additional operation of Zn/NH4 Cl via a two-step one pot process could further promote the cleavage of the C–O bond in β-O-4 units in lignin. And this reaction system was also applicable to native lignin as the molecular weight of native lignin decreased obviously as detected by gel permeation chromatography (GPC). Additionally, this is the first to date generation of the by-product H2 from native lignin and the by-product was straightforwardly captured by 1-decene. A probable mechanistic pathway was also proposed with the help of density functional theory (DFT) calculations.